The pearly white trend an in-depth look at tooth whitening - Segarra, Armin G. (The Journal of the Philippine Dental Association)
One of the common aesthetic procedures in dentistry is vital tooth bleaching or whitening for the correction of discolored teeth. This article will take a close look into the active agent/s of tooth whitening and its mechanis of action, when and where tooth whitening can be effective and successful, the different methods of teeth whitening, possible adverse reactions to the bleaching treatment and some recommendations on how to use it effectively.